Modes of faith : secular surrogates for lost religious belief - Ziolkowski, Theodore (University of Chicago Press, 2007)
In the decades surrounding World War I, religious belief receded in the face of radical new ideas such as Marxism, modern science, Nietzschean philosophy, and critical theology. Modes of Faith addresses both this decline of religious belief and the new modes of secular faith that took religion's place in the minds of many writers and poets. Theodore Ziolkowski here examines the motives for this embrace of the secular, locating new modes of faith in art, escapist travel, socialism, politicized myth, and utopian visions. James Joyce, he reveals, turned to art as an escape while Hermann Hesse made.